1997
DOI: 10.1152/ajpendo.1997.272.4.e712
|View full text |Cite
|
Sign up to set email alerts
|

Clenbuterol, a beta2-adrenoceptor agonist, reduces scoliosis due to partial transection of rat spinal cord

Abstract: Injury to the spinal cord often results in abnormal lateral curvature of the spine, or scoliosis, that is associated with neuromuscular weakness. The lateral curvature of the spine is thought to be a consequence of insufficient or asymmetrical loading of the vertebrae. To study neuromuscular scoliosis, an animal model of spinal cord injury was used in which the spinal cord was partially (3/4) transected, with the left lateral columns left intact. Partial transection of the spinal cord in the rat caused scolios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…␤-Agonist administration has been proposed as a strategy to attenuate the loss of muscle mass (and function) following denervation (6,7,19,137,213,241,279,281,480,483) or muscle unloading (4,110,376,450,476), with application to the muscle atrophy associated with plaster casting, joint pinning, or extended periods of weightlessness, such as during space flight.…”
Section: Denervation and Muscle Unloadingmentioning
confidence: 99%
“…␤-Agonist administration has been proposed as a strategy to attenuate the loss of muscle mass (and function) following denervation (6,7,19,137,213,241,279,281,480,483) or muscle unloading (4,110,376,450,476), with application to the muscle atrophy associated with plaster casting, joint pinning, or extended periods of weightlessness, such as during space flight.…”
Section: Denervation and Muscle Unloadingmentioning
confidence: 99%
“…Results from various animal models showed that clenbuterol can prevent muscle mass loss, although it remains unclear what its actions are at the single cell level in individual fibers (Zeman et al, 1997(Zeman et al, , 1999. Also, some tests have been conducted with testosterone in SCI patients, but mainly to study spermatogenesis, muscle strength, and locomotor recovery (Clark et al, 2008;Gregory et al, 2003;Huang et al, 1999).…”
Section: Effects On Muscle Fiber Type Distribution and Sizementioning
confidence: 99%
“…1,8,12,16,19,36,40,41 Consistent with increased muscle strength and loading, skeletal abnormalities including demineralization and scoliosis that result from neuromuscular weakness are also improved by ␤ 2 -agonist treatment. 38,39 The ability of ␤ 2 -agonists to reduce muscle atrophy and to stimulate hypertrophy may account for improved strength 36,37 in some neuromuscular diseases. On the other hand, the effects of ␤ 2 -agonists on muscle fiber necrosis and loss, a primary cause of weakness in muscular dystrophy, have not been determined.…”
mentioning
confidence: 99%